RACIAL TRAUMA AND SELF-DESTRUCTION: THE PSYCHOLOGICAL CONSEQUENCES OF DISCRIMINATION IN THE BLUEST EYE - Walunj, Jyoti Dnyaneshwar; Gadekar, Sachin (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This paper explores the psychological consequences of racial discrimination in Toni Morrison’s The Bluest Eye (1970), with a focus on racial trauma and self-destruction. This study explores how systemic oppression and internalised racism result in catastrophic mental and emotional collapse through an examination of important people, especially Pecola Breedlove. This paper uses literary and psychological frameworks to show how Morrison challenges systematic racism and how it affects African Americans’ self-perception and mental health.